Two-staged treatment for advanced keratoconus in children - Almodin,Edna Motta (2018)
Abstract We present a case of a 12-year-old patient with advanced keratoconus in both eyes who received a two-staged treatment in the right eye (OD) to decrease keratoconus progression rate and rehabilitate patient’s vision. At the initial clinical examination, visual acuity without correction in OD was count fingers; cycloplegic refraction was -22.00 - 7,50 x 100° = 20/400; corneal topography demonstrated a curvature of 64.28 x 105° / 55.38 x 15°; and tomography (WaveLight - Allegro Oculyzer) demonstrated a curvature of 68.1 x 114° / 63.3 x 163° Q = -2.67. Initially, the patient received an intrastromal ring segment (210 mm / 200 µm) slightly off center to avoid the thinnest part of the cornea. Six months later a phakic lens was implanted in the anterior chamber. At the follow-up visit 13 months after phakic lens implantation (19 months after ring implantation), visual acuity in OD was 20/20 without correction; cycloplegic refraction was -0.50 -0.75 x 180o = 20/20; and corneal topography showed keratometry of 63.22 x 44o / 61.10 x 134o. The results demonstrated that the associated procedures were successful in decreasing irregular astigmatism and markedly improving patient’s uncorrected visual acuity in OD, postponing the need for corneal transplantation to a more suitable age, if required.